Neutrophils and Lymphocytes: Yin and Yang of Lung Fibrosis and Patient Outcome in Diffuse Interstitial Lung Diseases - Erika M. Novoa-Bolivar; José A. Ros; Sonia Pérez-Fernández; José A. Campillo; Ruth López-Hernández; Rosana González-López; Almudena Otalora-Alcaraz; Cristina Ortuño-Hernández; Lourdes Gimeno; Inmaculada Ruiz-Lorente; Diana Ceballos-Francisco; Manuel Muro; et al. (Biomedicines)
Objective: Antifibrotics can improve the outcome of patients with idiopathic pulmonary fibrosis (IPF) and other fibrosing interstitial lung diseases (F-ILDs), but predictive biomarkers at diagnosis are needed to guide the use of immunomodulating and antifibrotic therapies. Methods: Flow cytometry quantification of lymphocytes and neutrophils in bronchoalveolar lavage (BAL) of 145 IPFs, 561 non-IPF-ILDs (125 F-ILDs), and 112 BAL controls were retrospectively correlated with the incidence of fibrosis and third-quartile overall survival (Q3–OS). Results: The incidence of IPF was directly proportional (9.6%, 22.2%, and 42.6%, p < 0.001) to BAL neutrophil counts (<5%, 5–15%, and >15%), but inversely proportional (34.1%, 18.6%, and 8.8%, p < 0.001) to BAL lymphocyte counts (<7%, 7–20%, and >20%). Elevated neutrophils (>5%) with low lymphocytes (<7%) were associated with an increasingly higher incidence of IPF (10.0–56.3%, p < 0.001) in patients aged 40 to 80, compared to the rest of patients (13.0–17.1%). Lymphocytes >20% compared to lymphocytes <7% strongly protected patients with neutrophils >15% (59.7% vs. 20.7%, p < 0.001) from IPF. In contrast, the incidence of F-ILD was not clearly related to BAL lymphocyte/neutrophil counts. Although, IPF and F-ILD showed a shorter Q3–OS (1.8 ± 0.3 and 4.6 ± 0.8 years; p < 0.001) than non-fibrotic-ILDs (11.1 ± 1.3 years), lymphocyte and neutrophil counts were associated with a longer and shorter Q3–OS of non-fibrotic-ILDs (p < 0.03) and F-ILDs (p < 0.04), respectively, but not with a Q3–OS of IPF patients (p < 0.708). Corticosteroids in patients with fibrosis showed a shorter Q3–OS than other immunomodulators (2.4 ± 0.3 vs. 4.0 ± 1.8 years, p = 0.011). Conclusions: Accurate counting of BAL lymphocytes and neutrophils by flow cytometry in ILD patients at diagnosis could help guide immunomodulatory and antifibrotic therapies.